Investigating the Professional Profile of Software Architects in Brazil using Job Advertisements - Lopes, Lais Cândido Rodrigues da Silva; Carvalho, Kaique Cruvinel; Kassab, Mohamad; Kalinowski, Marcos; OliveiraJr, Edson; Graciano Neto, Valdemar Vicente (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2025: Anais do XXXIX Simpósio Brasileiro de Engenharia de SoftwareDO - 10.5753/sbes.2025.10448, 2025)
Software systems are vital to industry, emphasizing the need for quality assurance. Software architecture underpins quality systems by reinforcing key requirements. However, defining the Software Architect role is still challenging, particularly in a dynamic market demanding complex systems. This emerging results paper investigates the profile sought for Software Architects in Brazil through an analysis of job ads collected from an online platform in October 2024. Of 411 ads, 286 were valid for analysis. The data revealed 191 different terms for the role, indicating a lack of standardization. The market favors candidates with formal education in IT and a broad skill set - ads listed an average of 11.4 skills, including APIs, Java, Azure, and DevOps. While planning and implementation tasks appeared in 69.5% of ads, activities like architecture management were less emphasized. Results also show a preference for in-person roles, and higher salaries were linked to degrees and on-site work. These findings help map employer expectations and reflect the diversity of the role in Brazil.